An immunochromatographic dipstick as an alternate for monitoring of heroin metabolites in urine samples. Issue 41 (26th June 2018) - Mishra, Priya; Banga, Ivneet; Tyagi, Roshika; Munjal, Tanya; Goel, Aditya; Capalash, Neena; Sharma, Prince; Suri, C. R.; Gandhi, Sonu
Abstract : Pathway of heroin degradation post oral administration in mice. Abstract : Heroin use and addiction pose serious risks and side effects due to overdose. Quantification of heroin in biological samples is challenging due to rapid deacetylation of heroin to its active metabolites. In this study, we report the quantification of metabolic degradation of heroin by-products in biological urine samples. The presence of the drug was monitored after oral administration of heroin at different time intervals. Various biophysical techniques, such as high performance liquid chromatography (HPLC) and mass spectrometry (MS) were used to evaluate the presence of the drug. A competitive fluorescence based immunoassay was developed with a limit of detection (LOD) up to 0.01 ng mL −1 and the IC50 value was 0.1 ng mL −1, while the dipstick assay shows a LOD up to 5 ng mL −1 . Rapid detection of narcotic drugs was carried out for biological urine samples collected at various time points. Validation of the developed dipstick was carried out for the standard as well as the spiked urine samples by fluorescence based immunoassay (FIA), using anti-morphine antibodies. A strong correlation ( R = 0.94) was obtained between the developed dipstick and FIA assay for biological urine samples collected at various time points. The developed immunochromatographic dipstick is highly sensitive, field applicable and cost effective, and can serve as a first choice for the monitoring of narcotic drugs in blood, urine and saliva in drug addicts and athletes.